Aptamer-conjugated gold nanoparticles and their diagnostic and therapeutic roles in cancer - Deng, Guozhen; Zha, He; Luo, Hongzhi; Zhou, Yi (Frontiers in Bioengineering and Biotechnology, 2023)
The burden of incidence rate and mortality of cancer is increasing rapidly, and the development of precise intervention measures for cancer detection and treatment will help reduce the burden and pain of cancer. At present, the sensitivity and specificity of tumor markers such as CEA and CA-125 used clinically are low, while PET, SPECT, and other imaging diagnoses with high sensitivity possess shortcomings, including long durations to obtain formal reports and the inability to identify the molecular pathological type of cancer. Cancer surgery is limited by stage and easy to recur. Radiotherapy and chemotherapy often cause damage to normal tissues, leading to evident side effects. Aptamers can selectively and exclusively bind to biomarkers and have, therefore, gained attention as ligands to be targeted for cancer detection and treatment. Gold nanoparticles (AuNPs) are considered as promising nano carriers for cancer diagnosis and treatment due to their strong light scattering characteristics, effective biocompatibility, and easy surface modification with targeted agents. The aptamer-gold nanoparticles targeting delivery system developed herein can combine the advantages of aptamers and gold nanoparticles, and shows excellent targeting, high specificity, low immunogenicity, minor side effects, etc., which builds a bridge for cancer markers to be used in early and efficient diagnosis and precise treatment. In this review, we summarize the latest progress in the application of aptamer-modified gold nanoparticles in cancer targeted diagnosis and delivery of therapeutic agents to cancer cells and emphasize the prospects and challenges of transforming these studies into clinical applications.